Metaphor and Metonymy in Poems of Anne Sexton - Diyah Feronika; Unpris Yastanti; Fitri Yeni (Center of Language and Cultural Studies [CLCS], 2023)
This research investigates the significance of metaphors and metonymies in shaping cognitive comprehension of abstract concepts by analysing Anne Sextonâ€™s poem â€œ45 Mercy Streetâ€. The research method employed for this research is descriptive qualitative with Lakoff and Johnsonâ€™s (2003) conceptual metaphor framework to identify three types of conceptual metaphor and the metonymy concept structure. The data is taken from the collection of the poems within the third part entitled â€˜The Divorce Paperâ€™ consist of seventeen poems. The result of this study indicates that: (1) a total of twenty-four metaphorical expressions were detected, with varying distributions among the three types of conceptual metaphor, namely two of orientational metaphor, nine ontological metaphors, and thirteen structural metaphors. (2) seventeen metonymical expressions are found distributed in seven metonymy concept structure which are five â€˜containers for contentâ€™, one â€˜material for objectâ€™, one â€˜controlled for the controllerâ€™, five â€˜parts for wholeâ€™, two â€˜places for eventsâ€™, one â€˜place for inhabitantsâ€™, and two â€˜producers for productâ€™